2017
DOI: 10.1007/s00167-017-4744-y
|View full text |Cite
|
Sign up to set email alerts
|

Neutral alignment leads to higher knee society scores after total knee arthroplasty in preoperatively non-varus patients: a prospective clinical study using 3D-CT

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 42 publications
4
85
1
Order By: Relevance
“…STA, SFA, mMPTA, and mLDFA belong to the angles of component alignment, while mMPTA and mLDFA determine the coronal alignments of the tibial and femoral components on the tibia and femur, respectively. Many studies [ 11 , 42 , 43 ] have proven that mMPTA and mLDFA were related to the post-operative function of the knee; our results were similar. In addition, we found that sagittal-plane component alignment, including SFA and STA, was weakly or not at all correlated with surgical outcome, similar to the findings of Antony J et al [ 21 ] DFVR was an individual anatomical characteristic and was not changed in TKA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…STA, SFA, mMPTA, and mLDFA belong to the angles of component alignment, while mMPTA and mLDFA determine the coronal alignments of the tibial and femoral components on the tibia and femur, respectively. Many studies [ 11 , 42 , 43 ] have proven that mMPTA and mLDFA were related to the post-operative function of the knee; our results were similar. In addition, we found that sagittal-plane component alignment, including SFA and STA, was weakly or not at all correlated with surgical outcome, similar to the findings of Antony J et al [ 21 ] DFVR was an individual anatomical characteristic and was not changed in TKA.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have demonstrated that an appropriate angle of implantation plays a pivotal role in clinical efficacy [ 5 9 ]. In the previous studies, the hip–knee–ankle angle (HKA) of the lower extremity within 3° and tibial and femoral implants perpendicular to their respective anatomical axes on the sagittal plane were considered the determining factors of surgical success [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malalignment of total knee arthroplasty (TKA) component positioning typically results in earlier component loosening and shortened survivorship of the prosthesis [1][2][3][4][5][6][7][8][9]. Deviations of more than 3° from neutral axis in the hip-knee-ankle axis (HKA) result in varus or valgus malalignment and are defined as 'outliers' when following an approach of classical mechanical alignment.…”
Section: Introductionmentioning
confidence: 99%
“…However, when it comes to knee arthroplasty for the sake of material durability as well as simplification of instrumentation and manufacturing the pioneers of total knee arthroplasty (TKA) have made numerous assumptions, which for centuries have not been questioned as a whole. In the last years, the dogma that all knees should have a neutral hip-knee-ankle angle (HKA) after TKA has been questioned for native varus knees [11]. In addition, there is an ongoing discussion about the optimal alignment in TKA [3,5,[8][9][10].…”
mentioning
confidence: 99%